Advanced Manufacturing Processes : Selected Papers from the Grabchenko's International Conference on Advanced Manufacturing Processes (InterPartner-2019), September 10-13, 2019, Odessa, Ukraine /: Selected Papers from the Grabchenko's International Conference on Advanced Manufacturing Processes (InterPartner-2019), September 10-13, 2019, Odessa, Ukraine. (2020) - Unknown
No abstract available